Geographical science in the school: principles for a curriculum based on disciplinary knowledge - Sonia Maria; Daniel (Uni-pluriversidad, 2015)
Discussions about the different kinds of knowledge that constitute the curriculum gain an increasingly remarkable importance, especially when placed in this debate issues relating to the role of schools nowadays. Within this context, this article seeks to gather some points of reflection on the role of disciplinary knowledge in the definition of the Geography curriculum at school, as well as its relationship with the knowledge from the lived world by the students. All the reflections listed here is originated from a research project developed by the authors, which seeks to better understand the role of scientific knowledge to defining and legitimizing the curriculum of Geography in school. Building on the theorical framework offered by Basil Bernstein and Michael Young, and the foundations of constructivist theories, we propose the rescue of scientific knowledge as the beacon of curriculum establishment at school, seen here as a set of “powerful knowledge” capable of provide students with effective conditions to perceive reality in their surroundings and to intervene in it.